Heterosis, Combining Ability and Their Inter-Relationship for Morphological and Quality Traits in Yellow Maize (Zea mays L.) Single-Crosses Across Environments - T. N. Bhusal; G. M. Lal (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
The research aimed to study heterosis, combining ability and performance along with their inter-relationship across three environments. Variance due to general (GCA) and specific combining abilities (SCA) and their interaction with environment was found to be significant for most of studied traits. For all the studied traits but ASI (Anthesis-silking interval), HI (Harvest index) and starch content, additive gene action was highly important than non-additive gene action for their expression as reflected by Baker's ratio which was near to unity. CML439, R13-1-1 and Tarun83-1-3-2 were the best general combiner for starch, protein and oil, respectively. R13-1-17, CML439 and Tarun83-1-3-2 were good general combiner for maturity characters and harvest index while TSK 196 and TSK 197 were good general combiner for cob length, cob girth, number of grains/row and grain yield. DMR9047×R13-1-17 and POP31Q×Tarun83-1-3-2 showed desirable heterosis and SCA effect for maturity characters. Regarding to SCA and heterosis, the prominent hybrids for grain yield were TSK197×R13-1-10, TSK194×POP31Q, DMR9047×POP31Q and R13-1-1×DMR9047. SCA established stronger relationship with per se performance of grain yield and quality traits than mid-parent (MPH) and best-parent heterosis (BPH), reflecting that an improvement in selection of SCA will results in an indirect improvement of MPH and BPH of hybrids.